2009
DOI: 10.1158/0008-5472.can-08-3513
|View full text |Cite
|
Sign up to set email alerts
|

Telomere Length in Peripheral Blood Predicts Survival in Clear Cell Renal Cell Carcinoma

Abstract: Telomeres are repetitive structures located at chromosome ends. Previous studies have indicated that blood cell telomeres may serve as a biomarker for cancer risk. In addition, we recently reported that blood telomere length predicted survival in patients with breast cancer. In the present study, we examined whether blood telomere length may act as a predictor for survival in newly diagnosed patients with clear cell renal cell carcinoma. Furthermore, we analyzed telomere length in tumor samples and correspondi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
83
3
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(93 citation statements)
references
References 35 publications
6
83
3
1
Order By: Relevance
“…Our findings differ from those of multivariate analysis findings in a longitudinal population-based study of cancer-free individuals (19), and studies of recently diagnosed cancer patients (37, 38) that found telomere length was associated with cancer mortality. Discrepancies in findings may be due to differences in telomere length assessment methodology, tumor type and telomere length response to different types of cancer disease.…”
Section: Discussioncontrasting
confidence: 99%
“…Our findings differ from those of multivariate analysis findings in a longitudinal population-based study of cancer-free individuals (19), and studies of recently diagnosed cancer patients (37, 38) that found telomere length was associated with cancer mortality. Discrepancies in findings may be due to differences in telomere length assessment methodology, tumor type and telomere length response to different types of cancer disease.…”
Section: Discussioncontrasting
confidence: 99%
“…Telomere shortening has been associated with various cancers, including bladder, small cell lung, basal cell, esophageal, and papillary thyroid cancers (15)(16)(17)(18)(19)(20). Longer telomeres have been associated with clear cell renal carcinoma (21). Several studies have examined lymphocyte telomere length in relation to breast cancer risk with conflicting results.…”
Section: Introductionmentioning
confidence: 99%
“…Once considered as a mere remnant of the proliferative history of the neoplastic clone, this feature is currently considered to play a role in establishing the malignant phenotype. Again, this notion is supported by the clear association between telomere length and prognosis in most human cancers [72][73][74][75][76][77][78][79][80][81]. There are a number of potential outputs linking telomere shortening and malignant phenotype.…”
Section: Telomere Deregulation In Cancer Developmentmentioning
confidence: 99%